Dzielimy się doświadczeniem Leiomyosarcoma of the pulmonary artery – a difficult diagnostic problem, uncertain prognosis - Jarek, Dariusz; Stanisławski, Ryszard; Mak, Marek; Klausa, Filip; Skiba, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2005)
Background: Primary malignant neoplasms of the heart and blood vessels are extremely rare, including leiomyosarcoma of the pulmonary artery, which affects mainly men in the 5–6 decade of life. But it is not an uncommon diagnosis among younger population. Growth of the sarcoma causes differently intensified symptoms of the right ventricle’s insufficiency and clinical features of chronic pulmonary embolism. Case study: A young female was admitted to the hospital with suspected infections endocarditis of the atypical course. During echocardiography pendulating structures in the pulmonary artery and its branches were found. Due to the risk of acute pulmonary embolism, the patient underwent urgent surgery. During histopathological examination of the resected material, leiomyosarcoma was identified. Chemotherapy was used as supplementary treatment. During a control examination with angio-CT after the course of treatment, atypical infiltrations in the stem and right branch of the pulmonary artery were observed. The patient was re-operated, during which thrombendarterectomy of appropriate pulmonary blood vessels was carried out. In the resected material, the histopathologist discovered only scar tissue. Control imaging examinations, carried out in three month intervals, did not reveal any pathological masses in the lumen of pulmonary blood vessels. Conclusions: Surgical treatment of leiomyosarcoma of the pulmonary artery, using the widest possible resection techniques associated with chemotherapy, greatly increases the chance of full recovery.